Recent advances in naturally fractured reservoir modeling - Ordoñez, A.; Peñuela, G.; Idrobo, E. A.; Medina, C. E. (CT&F - Ciencia, Tecnología y Futuro, 2001)
Large amounts of oil reserves are contained in naturally fractured reservoirs. Most of these hydrocarbon volumes have been left behind because of the poor knowledge and/or description methodology of those reservoirs. This lack of knowledge has lead to the nonexistence of good quantitative models for this complicated type of reservoirs. The complexity of naturally fractured reservoirs causes the need for integration of all existing information at all scales (drilling, well logging, seismic, well testing, etc.) to provide a reservoir description for such reservoirs. This paper presents an overview of recent advances in naturally fractured reservoir modeling, which were developed to characterize the dual porosity system and to improve hydrocarbon recovery. Two techniques, material balance and numerical simulation, are shown to be supportive of one another. The material balance technique is a good tool for history matching of production performance and defining the system, which is then used as input in the numerical model. However, material balance has significant disadvantages when it comes to prediction, which is the domain of numerical simulation modeling. We present the application of a recently introduced material balance equation based on a dual-system approach. In numerical simulation, the mathematical model to predict fluid flow in anisotropic media is enhanced by using permeability tensors. We also discuss a technique to construct permeability tensors from seismic, well log and well test analysis.